The Role of Strategic Leadership in Encouraging Innovative Culture in Islamic Education Institutions - Ummi Hani’; Misbahul Arifin; Ahmad Sahidah; Uthman Shehu Lawal (Journal Of Social Siences And Islamic Studies (JOSIS), 2025)
This research focuses on the role of strategic leadership in building an innovative culture in Islamic educational institutions, by taking a case study at Pondok Pesantren Al Mashduqiah Kraksaan, Probolinggo Regency. The primary purpose of this research is to identify how strategic leadership practices can encourage the growth of innovation in the learning system and institutional management of pesantren. This research employed a qualitative approach, utilizing a case study design, and data were collected through in-depth interviews, participatory observation, and documentary studies.The research informants consisted of pesantren leaders, madrasah heads, teachers, and senior santri. The results showed that strategic leadership in the pesantren environment is reflected in four main aspects: support for educational experiments, commitment to human resource development, exemplary innovative values, and participatory communication strategies. These four aspects form an ecosystem conducive to the emergence of new ideas and the improvement of educational quality. The implications of this study show that in the context of pesantren, visionary, adaptive, and value-based leadership can encourage institutional transformation without leaving the roots of Islamic tradition. Therefore, this strategic leadership model is relevant to be applied more broadly in the development of Islamic education institutions in the contemporary era